Foot Kinematics and Neuromuscular Preactivation in Habitual Forefoot and Rearfoot Runners - (:unkn) unknown (My University, 2016)
As the rate of running related injuries has failed to decline despite advances in footwear, many researchers have begun focusing on different foot strike patterns possible contribution to injury risk. While many studies have focused on the differences between RFS and FFS running, few have investigated kinematic differences within the distal foot in habitual RFS and FFS runners and have failed to consider mechanical and neuromuscular changes due to fatigue. The purpose of this study, therefore, was to investigate foot kinematics and neuromuscular differences between RFS and FFS runners at the beginning and end of an exhaustive run. Fifteen habitual RFS and 15 habitual FFS runners (27.6 ± 5.64 years) performed a maximal 5 km treadmill run. A seven segment foot model was used with 3D motion capture methods to calculate joint kinematics of six functional articulations: rearfoot, calcaneonavicular, calcaneocuboid, medial forefoot, lateral forefoot, and first metatarsophalangeal (MTP). Four dual Ag/AgCl EMG surface electrodes were attached to the medial gastrocnemius, peroneus longus, soleus, and tibialis anterior to identify neuromuscular activity. Motion capture and EMG data were analyzed for five consecutive steps at the beginning and end of the 5 km run. Motion capture data was processed to investigate foot kinematic and joint coordination variability differences between the foot strike patterns at the beginning and end of the 5 km run. EMG data was processed to investigate neuromuscular preactivation onset and magnitude (iEMG) differences between the foot strikes at the beginning and end of the run. Mixed between-within groups statistical tests were used to compare variables between the foot strike patterns at the beginning and end of the exhaustive run. Exploration of kinematic results indicated a more supinated foot in FFS runners at initial contact and through early stance. The increased foot supination may result in a more rigid foot, but a less stable ankle joint. When the foot is moving toward greater pronation, a greater demand on soft tissues for stability is expected which may imply increased risk of soft tissue injury within the foot for RFS runners. Both groups demonstrated an increased range of motion at the end of the run during the first (0-20% of stance), 3rd (51-75% of stance), and 4th (76-100% of stance) stance subphases which may be a result of muscular fatigue and may increase injury risk to dynamic stabilizers of the foot articulations. With respect to joint coordination, rearfoot-midfoot coupling variability increased in both groups during midstance (21-50% of stance) at the end of the run. The increased variability may have been indicative of neuromuscular compensation to alter step-to-step variability in order to avoid overstressing tissues which may lead to overuse injury. Neuromuscular preactivation magnitude was increased and occurred earlier in the tibialis anterior in RFS runners and preactivation onset was earlier in the gastrocnemius in FFS runners. While RFS runners require tibialis anterior activation to maintain a dorsiflexed position at initial contact, it is likely that the earlier gastrocnemius onset in FFS runners facilitates positioning of the foot for initial contact with the forefoot. The earlier gastrocnemius onset in FFS with no significant difference in magnitude may suggest different roles of the gastrocnemius between the foot strikes and may be clinically relevant when looking at overuse injury risks. There was no difference in neuromuscular preactivation as a result of the 5 km run, suggesting that neuromuscular fatigue did not affect how the muscles prepared for initial contact.
Keywords: Foot Strike; Joint Coupling; Minimalist Shoes; Multi-segment Foot Model; Preactivation; Running